Rb family-independent activating E2F increases genome stability, promotes Homologous Recombination, and decreases Non-Homologous End Joining - Pei, Xun (Mech Dev, 2020)
The retinoblastoma protein Rb is a prototype tumor suppressor inactivated in a variety of cancers. In addition to deregulated cell proliferation, Rb inactivation also causes genome instability that contributes to tumorigenesis. Although the genome instability effects of Rb inactivation was shown to be mediated mainly by E2F-independent mechanisms, little is known about whether the constitutive free activating E2F proteins released by Rb-inactivation affects genome stability. In this manuscript, we take advantage of the dE2F1(su89) mutant, which contains a point mutation in the conserved Rb-binding domain that disrupts its interaction with the Rb family proteins, to characterize the effect of constitutive free activating E2F on genome stability in the presence of WT Rb. We showed that dE2F1(su89) promoted genome stability in the mwh genome stability assay. We found that the genome stability effects of dE2F1(su89) was sensitive to the levels of activating E2F activity and to the levels of E2F targets involved in DNA replication and repair but not to the level of E2F cell cycle target Cyclin E. Importantly, we showed that dE2F1(su89) promoted DNA double-strand break (DSB) repair by homologous recombination and decreased DSB repair by Non-homologous end joining (NHEJ). These results show that the constitutive free activating E2F promotes genome stability, which potentially contributes the observed tumor development in E2F1 knockout mice and the reported NHEJ defects in Rb mutant cells. These results also explain why constitutive free activating E2F alone was not sufficient for tumor development.